MiR-125b Suppression Inhibits Apoptosis and Negatively Regulates Sema4D in Avian Leukosis Virus-Transformed Cells - Ren, Chaoqi (Viruses, 2019)
Subgroup J avian leukosis virus (ALV-J), an oncogenic retrovirus, causes hemangiomas and myeloid tumors in chickens. We previously showed that miR-125b is down-regulated in ALV-J-induced tumors. This study aimed to investigate the possible role of miR-125b in ALV-J-mediated infection and tumorigenesis. Knockdown of miR-125b expression in HP45 cells reduced, whereas over-expression induced late-stage apoptosis. Bioinformatics analysis and luciferase activity assays indicate that miR-125b targets Semaphorin 4D/CD100 (Sema4D) by binding the 3′-untranslated region of messenger RNA (mRNA). Up-regulation of miR-125b in the DF1 cell line suppressed Sema4D expression, whereas miR-125 down-regulation increased Sema4D expression levels. To uncover the function of Sema4D during ALV-J infection, animal infection experiments and in vitro assays were performed and show that Sema4D mRNA levels were up-regulated in ALV-J-infected tissues and cells. Finally, functional experiments show that miR-125 down-regulation and Sema4D over-expression inhibited apoptosis in HP45 cells. These results suggest that miR-125b and its target Sema4D might play an important role in the aggressive growth of HP45 cells induced by avian leukosis viruses (ALVs). These findings improve our understanding of the underlying mechanism of ALV-J infection and tumorigenesis.